Estimativa da elasticidade-renda do consumo de carnes em nove regiões metropolitanas do Brasil empregando dados em painel - Carbonari, Thiago (2010)
There are several variables that can influence meat consumption. Among these variables, we must give a lot of importance to the income of the population. Due to this fact, this study tried to measure the impact that the average monthly household income has on the human consumption of beef, pork and poultry in nine metropolitan areas of Brazil. For this, it was calculated the coefficients of the income elasticity for the human consumption of these types of meat, by using panel data. The data are from the POFs( 1987-1988),(1995-1996), (2002- 2003) , published by IBGE, and the calculations of the coefficients were peformed with the aid of statistical software Eviews. The fresh beef, followed by pork, stew meat and chicken, was the one that had the highest rates of the income elasticity in general. This shows that the fresh beef and the pork have the greatest potential for the growth of consumption than the others, in case the income of the Brazilian population increases. The use of panel data, with fixed effects and time for the calculation of the income elasticities, enabled to capture possible differences in the consumption of the studied meat in the nine surveyed metropolitan areas and checked if there was any change in the pattern of meat consumption among the POFs used as a primary source of data for this work as well